Experimental and CFD study of sodium alginate droplets impacting onto immiscible deep liquid surface. (11th May 2021) - Chen, Chengmin; Ding, Zhizhong; Tiwari, Shashank S.; Wang, Jianmei; Wang, Jianchun; Liu, Guangxia; Li, Yan; Guo, Meng; Nandakumar, Krishnaswamy
Abstract: In the present study, the impingement process of alginate droplet on an immiscible liquid is investigated using experimental and numerical approaches. The results reveal that the intensity of interaction between the two immiscible liquids leads to formation of different droplet shapes after impingement. The droplet yield stress, Ohnesorge number ( Oh ), and Weber number ( We ) were found to be the chief parameters which determine the droplet shape after impingement. Three discernible shapes of droplets could be identified from the present investigation: (i) spherical ball, (ii) spherical ball with a tail, and (iii) a toroidal shape. A detailed parameter regime map has been constructed which aids in identifying these three droplet shapes in well‐defined range of Oh and We . Besides, the numerical investigations carried out also helped in deciphering the temporal evolution of the pressure, velocity and kinetic energy fields associated with the drop impingement process.